Efectos de un plan de aprendizaje estructurado mediante la práctica por bloques en el golpeo con la parte interna del pie en niños de 10 a 12 años de edad (2010)
ABSTRACT: In this paper were analyzed the effects of a training (learning) plan through block practice in the inner-edge-of-the-foot-strike soccer techniques on the acquisition (learning) of these technical fundament. The research was conducted with a sample of nine children between 10 and 12 years of age belonging to a soccer club. The study was conducted with one experimental group, randomly formed, who conducted a pre-test - postest. To make the assessment, it was previously designed and structured measurement instrument of learning and it were used film records for each subject. For data processing were used central tendency, dispersion and inference measures. Results show that after the implementation of a plan of technical learning (1.000 repetitions of technical fundament) statistically significant differences in learning for technical fundament were presented.